The Story of a Forbidden and Censored Book: Early Editions of Evliya celebi's Seyahatname - (:unkn) unknown (ISTANBUL 29 MAYIS UNIV & ISAM, 2015)
Evliya celebi's Seyahatname (Book of Travels) did not receive much attention until the nineteenth century: From this century onwards, it gradually became a popular work thanks to, first, the Muntehabat composed by Hammer in English and then to a compilation of excerpts in Turkish. Encouraged by this interest, Ahmed Cevdet, the owner of Ikdam newspaper, set out to publish the ten volumes of the Seyahatname. Although incomplete, censored and sometimes incorrect, he managed to publish the first six volumes between 1896-1901. Because of the complaints against the Seyahatname, he then had to stop printing and was obliged to lock the printed volumes in storehouses. Although both the Muntehabat-i Evliya celebi and the first six volumes that Ahmed Cevdet published were banned by government, they helped expanding the Seyahatname's readership. This article discusses the Ottoman Turkish editions of Evliya celebi's Seyahatname, which were instrumental in conveying the work to large masses and also effectively forming a negative public opinion about both the work and its author.
Keywords: Evliya celebi; Seyahatname; Muntehabat-i Evliya celebi; Ikdam; Ahmed Cevdet